A Legal Perspective of the Regulatory Framework for Trado-Medical Practice in Nigeria - Ayemere, Eric; Enakemere, Lucky Ehimen (Kathmandu School of Law Review, 2014)
The authors are of the view that based on the good services provided by genuine trado-medical practitioners; this form of healing art should be encouraged under a strict regulatory regime in order to avoid the dangers prevalent where there is a lack of effective regulations. The article analyses the legal and institutional framework of trado-medical practice in Nigeria and examines the constitutionality of the extant National and some States legal regime if any and its impact in effectively and positively facilitating tradomedical practice in Nigeria. This article also contends that presently, there is no comprehensive regulation due to the absence of specific National legislations on the trado-medical practice. Governments all over the world are increasingly embracing and recognizing Trado-medical practice which been propelled by the fact that many diseases which have prove resistant to orthodox medicine requires attention from alternative therapy. The challenge of adopting trado-medical practice into the mainstream health care sector is that it is not backed with a specific legislation regulating its practice and practitioners. This paper finally conclude that unless there is an urgent and positive change in the attitude of Government coupled with a vigorous political will to strengthen the present legal and institutional framework, patronage of traditional medicine in Nigeria will not be guaranteed as to the safety of the patient and trado-medical practice which is rooted in our culture and heritage will be lost.